Clinical Presentation and Treatment Outcome of Abdominal Tuberculosis - Rahman, Oliur; Kabir, Anwarul; Biswas, Prodip Kumar; Islam, AMM Shoriful; Siddik, AB; Rahman, Habibur (Journal of Medicine, 2014)
Background: Tuberculosis is common in our country. It commonly affects the lungs but in up to one third of the cases involve other organs. Abdominal tuberculosis is one of the important extrapulmonary tuberculosis.It has varied presentation, frequently mimicking other common and rare diseases. Materials and Methods:It is a prospective observational study done to see the clinical presentation and treatment outcome of abdominal tuberculosis in medicine, surgery and gastroenterology department Sylhet M A G Osmani Medical College Hospital during Jan 2008-Dec2008. Sample was collected purposively. All patients were undergone detailed history, clinical examination, relevant investigation and follow up till the end of six months anti tubercular chemotherapy.Data recorded in predesigned record form. Statistical analysis was done with SPSS software. All data presented as percentage or mean. Result: From the 50 cases of abdominal TB, 26 (52%) were male and 24 (48%) were female. Male and female ratio was 1.04:1. Here most of the patients were in the age of 21-30 years and mean age was 29.3 years,majority of them were from poor socioeconomic status(18%) had associated pulmonary tuberculosis.The common presentation exhibited by the patients were weight loss (100%), low grade fever (88%), abdominal pain (86%), bowel disturbance (84%), anorexia (80%), nausea and vomiting (70%), abdominal distension (46%), , ascites (42%).Most of the patients were anaemic with raised ESR.Ultrasonography revealed ascites,abdominal lymphadenopathy and thick walled bowel. Colonoscopy found nodularity and ulceration with narrowing. Ascitic fluid was exudative with predominant lymphocyte count. Laparoscopy and laparotomy revealed tubercle on the intestine and the mesentery with thickening and bowel stricture. All the biopsy reports were consistent with tuberculosis. Site of involvement in decreasing frequency were ileocaecal (44%), peritoneal (16%), abdominal lymph node (8%), ascending colon (8%), small bowel (6%),transverse colon (4%), sigmoid colon (2%), rectum (2%), gastric (2%) and duodenal (2%) but multiple site in 6%.The treatment was given as per the WHO guidelines with category I drugs and found- 86% cured with anti TB alone, 4% needed surgery for intestinal obstruction along with anti TB, and 10% drop out from follow up. Conclusion:The clinical presentations of abdominal TB appear not specific for the condition. Thus, careful approach and supportive results are required in order to issue the final diagnosis. If diagnosed early, it can be treated successfully with the conventional anti-TB drugs. DOI: http://dx.doi.org/10.3329/jom.v15i2.20686 J MEDICINE 2014; 15 : 131-134